Structures and functions of short argonautes - Chen Wang; Zhangfei Shen; Xiao-Yuan Yang; Tian-Min Fu (RNA Biology)
Argonaute proteins (Agos) represent a highly conserved family of proteins prevalent in all domains of life and have been implicated in various biological processes. Based on the domain architecture, Agos can be divided into long Agos and short Agos. While long Agos have been extensively studied over the past two decades, short Agos, found exclusively in prokaryotes, have recently gained attention for their roles in prokaryotic immune defence against mobile genetic elements, such as plasmids and phages. Notable functional and structural studies provide invaluable insights into the underlying molecular mechanisms of representative short Ago systems. Despite the diverse domain arrangements, short Agos generally form heterodimeric complexes with their associated effector proteins, activating the effector’s enzymatic activities upon target detection. The activation of effector proteins in the short Ago systems leads to bacterial cell death, a mechanism of sacrificing individuals to protect the community.